Study of residual stress in a thin platinum layer by means of nondestructive x-ray diffraction - Bollhofer, Axel (Department of Physics, 2023)
Resistance thermometers are often made of thin, sputter-deposited platinum layers on a corundum substrate. Since such thermometers are usually exposed to extreme temperatures, residual stress is building up at the Pt-Ah03 interface and can possibly damage the layer. Therefore, the stress in the layer is measured by means of non-destructive x-ray diffraction and evaluated by the frequently used "d-sin21/J" method. The apparatus for the measurements was a Q-goniometer with a Bragg-Brentano focusing beam arrangement and a position sensitive detector. X-ray fluorescence scans were also performed on the sample in order to gain information about its composition. Additionally, a scanning-electron-microscope was used to investigate its microstructure. The crystallographic texture of the platinum was also examined by x-ray diffraction and displayed in pole figures.